복합효소제 첨가 및 고체상태 발효가 채종박의 in vitro 소화율 및 단쇄지방산 생성에 미치는 효과 - 구성민; 이에스더; 전현수; 이수협; 장재철; Seong Min Koo; Esther Lee; Hyeon Su Jun; Su Hyup Lee; Jae Cheol Jang (농업생명과학연구, 2024)
본 실험에서는 외인성 효소 첨가제 및 혼합 세균 배양을 통한 고상발효(Solid-state fermentation, SSF)가 채종박(Rapeseed meal, RSM)의 체외건물소화율(In vitro dry matter digestibility, IVDMD) 및 단쇄지방산(Short chain fatty acid) 생성에 미치는 영향을 조사하기 위해 수행되었다. 외인성 효소 칵테일(첨가 및 미첨가) 및 RSM에 대한 SSF(발효 및 비발효)를 나타내는 2 x 2 요인 설계가 적용되었다. 3-step 돼지 소화율 모델을 적용하여 채종박의 건물 소화율을 분석하였으며, 72시간 대장발효 후 상층액을 수집하여 단쇄지방산 생성량을 분석한 후 칼로리 단위로 변환하여 가소화에너지 소화율을 분석하였다. 소장 (IVDMDh) 및 전장 (IVDMDt) 건물소화율에서는 고상발효된 채종박이 더 높게 나타났다 (각각 p < 0.01). 마찬가지로, 외인성 효소 첨가제 처리구에서 채종박의 소장 소화율(IVDMDh)이 증가하는 경향을 나타냈다(p = 0.06). Acetic acid 및 butyric acid의 생산은 대조구에 비해 고상발효 처리 시 유의하게 더 생산되었으며 (각각 p < 0.01), 이는 총 단쇄지방산의 생산 증가 경향을 나타냈다(p = 0.09). 에너지 소화율에서는 채종박의 고상발효 및 외인성 효소제 첨가가 유의적으로 높게 나타났다 ( p < 0.01). 그러므로 채종박의 고상발효 처리는 단백질 이용성을 비롯한 영양적 가치를 향상시키는데 효과적이라고 사료된다. An experiment was carried out to investigate the effect of exogenous enzyme supplementation and solid-state fermentation (SSF) with a mixed bacterial culture on in vitro dry matter digestibility (IVDMD) and short chain fatty acid (SCFA) production of rapeseed meal (RSM). A two-factor factorial design was applied indicating 1) exogenous enzyme cocktail (supplemented and non-supplemented), 2) SSF (fermented and non-fermented) applied to RSM in vitro. After 48 hours at 37°C of SSF process, fermented RSM was collected and hydrolyzed in two steps using pepsin and pancreatin to calculate IVDMD. In the following step, the hydrolyzed residues were filtered, dried, and pooled before being incubated in a mineral-buffered solution with fresh feces. Upon filtering fermentation residues, SCFA concentrations in the supernatant were determined and residues were determined for total tract IVDMD. The IVDMD from simulated gastric and small intestinal hydrolysis (IVDMDh), and total tract IVDMD (IVDMDt) were greater for SSF in RSM (p < 0.01, respectively). Similarly, there was a trend for increasing IVDMDh for Multi-Enz in RSM (p = 0.06). Production of acetic acid, and butyric acid were greater for SSF (p < 0.01, respectively) compared with non-SSF in RSM. SSF of RSM tended to increase total SCFA production (p = 0.09). In vitro digestibility of gross energy digestibility (IVDGE), and calculation of gross energy based on IVDGE were was greater in both SSF (p <0.01), and Multi-Enz (p <0.01), respectively. The results of this study indicate that SSF enhances protein quality, which may be effective in improving IVDMD and IVDGE.